2013
DOI: 10.1091/mbc.e12-12-0846
|View full text |Cite
|
Sign up to set email alerts
|

An analogue-sensitive approach identifies basal body rotation and flagellum attachment zone elongation as key functions of PLK inTrypanosoma brucei

Abstract: The Polo-like kinase homologue in Trypanosoma brucei (TbPLK) regulates the assembly of a series of organelles necessary for positioning the parasite's flagellum. An analogue-sensitive strategy is used to acutely and specifically inhibit the kinase with a small molecule, making it possible to identify novel TbPLK functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 58 publications
(102 reference statements)
3
39
0
Order By: Relevance
“…However, whether TbPLK plays a role in basal body duplication is still controversial. One report suggested that TbPLK is required for basal body duplication (31), whereas other studies showed that TbPLK is required for segregation/rotation, but not duplication, of the basal body (30,32).…”
mentioning
confidence: 99%
“…However, whether TbPLK plays a role in basal body duplication is still controversial. One report suggested that TbPLK is required for basal body duplication (31), whereas other studies showed that TbPLK is required for segregation/rotation, but not duplication, of the basal body (30,32).…”
mentioning
confidence: 99%
“…TbPLK localization has been shown to be dynamic through the cell cycle. Consistent with its lack of mitotic function, TbPLK does not localize in the nucleus, but is found at the basal bodies, the bilobe structure, the flagellar pocket collar, and the flagellum attachment zone [82][83][84][85][86]. TbPLK regulation, although appearing to be divergent in many aspects, does -in common with other PLKs -require phosphorylation of threonine residues in the activation loop for full kinase activity [87].…”
Section: Polo-like Kinasesmentioning
confidence: 95%
“…Studies characterizing TbPLK function found the kinase to be essential in PCF and BSF T. brucei, but no evidence to date suggests that TbPLK plays a role in mitosis. Instead, TbPLK is essential for basal body rotation and kinetoplast DNA segregation, [80][81][82]83], Golgi biogenesis [84], bilobe duplication via phosphorylation of TbPLK's only known in vivo substrate, Tb Centrin2 [84,85] and flagellum inheritance in PCF parasites [82,83,85] and for furrow ingression during cytokinesis in the BSF stage [81]. TbPLK localization has been shown to be dynamic through the cell cycle.…”
Section: Polo-like Kinasesmentioning
confidence: 99%
“…While a few human and T. brucei PKs have residues as small as threonine at this location, the large majority of PKs utilize methionine, leucine or phenylalanine. Although this is not always the case (Oh et al, 2007; Lopez et al, 2014), some PKs tolerate mutation of the gatekeeper residue to small glycine or alanine residues, which enlarges the size of the ATP-binding site (Johnson et al, 2008; Hengeveld et al, 2012; Lourido et al, 2012; Lozano-Nunez et al, 2013). This creates an analog-sensitive PK (as-PK) which can be specifically inhibited by ATP-competitive inhibitors that contain bulky side chains (called bumped kinase inhibitors, BKIs), unlike the wild-type (WT) PK (Liu et al, 1999).…”
mentioning
confidence: 99%
“…This chemical genetic approach is similar to therapeutic application of drugs, since the PK is present but inactivated with an ATP-competitive inhibitor, rather than absent as with genetic approaches such as RNA interference (RNAi) or conditional knockouts (cKOs). To our knowledge this approach has been successfully applied in one instance thus far to study the cellular function of a kinetoplastid PK, the polo-like kinase of T. brucei (Lozano-Nunez et al, 2013), but has not yet been used for in vivo studies of parasite infection.…”
mentioning
confidence: 99%